Classics of children's literature - Frey, Charles H.; Griffith, John W. (Macmillan, 1987)
Presents some of the "masterpieces" of children's literature, including Mother Goose verses, fairy tales, works by Lear, Ruskin, Carroll, Twain, Stevenson, Baum, Grahame, Kipling, Dickens, Wilder, and more.